Epistasis for head morphology in Drosophila melanogaster. Issue 10 (13th August 2021) - Özsoy, Ergi D; Yılmaz, Murat; Patlar, Bahar; Emecen, Güzin; Durmaz, Esra; Magwire, Michael M; Zhou, Shanshan; Huang, Wen; Anholt, Robert R H; Mackay, Trudy F C
Abstract: Epistasis—gene–gene interaction—is common for mutations with large phenotypic effects in humans and model organisms. Epistasis impacts quantitative genetic models of speciation, response to natural and artificial selection, genetic mapping, and personalized medicine. However, the existence and magnitude of epistasis between alleles with small quantitative phenotypic effects are controversial and difficult to assess. Here, we use the Drosophila melanogaster Genetic Reference Panel of sequenced inbred lines to evaluate the magnitude of naturally occurring epistasis modifying the effects of mutations in jing and inv, two transcription factors that have subtle quantitative effects on head morphology as homozygotes. We find significant epistasis for both mutations and performed single marker genome-wide association analyses to map candidate modifier variants and loci affecting head morphology. A subset of these loci was significantly enriched for a known genetic interaction network, and mutations of the candidate epistatic modifier loci also affect head morphology.